Syndrome in question - Nascimento, Ana Claudia Mendes do [UNESP]; Gaspardo, Daniela Barros Cortez [UNESP]; Cortez, Tatiana Mimura [UNESP]; Miot, Helio Amante [UNESP] (Sociedade Brasileira de Dermatologia, 2014)
The authors present a male 40-year-old patient with established diagnosis of Behçet's disease which had evolved to recurrent bilateral auricular polychondritis crises. MAGIC syndrome (mouth and genital ulcers with inflamed cartilage) is rare and groups together patients with this clinical picture without necessarily fulfilling the clinical criteria for Behçet's disease or relapsing polychondritis, demonstrating an independent disorder.
Keywords: Behcet syndrome; Polychondritis; Relapsing; Stomatitis; Aphthous; Vasculitis